The Right of Political Opposition in Islamic History and Legal Theory: An Exploration of an Ambivalent Heritage - Alibasic, Ahmed (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Right of Political Opposition in Islamic History and Legal Theory: An Exploration of an Ambivalent Heritage